Molecular identification and preliminary diversity analysis of Astylus atromaculatus Blanchard, 1843 (Coleoptera: Melyridae) based on mitochondrial COI sequences - Arneodo Larochette, Joel Demian; Decker Franco, Cecilia (Springer, 2024)
Astylus atromaculatus Blanchard, 1843 (Coleoptera: Melyridae) is a pollinivorous beetle native to southern South America, which has invaded South Africa more than a century ago. Adults and/or larvae may occasionally damage flowers, seeds, and seedlings of various crops. Severe cattle intoxication has also been reported in Argentina, Uruguay, and South Africa following consumption of alfalfa and forage grasses infested with A. atromaculatus. Despite its economic impact, essential genetic information is lacking for this species. The present paper provides the first DNA barcode reference sequences for A. atromaculatus based on the standard 5’ fragment (658 bp) of the cytochrome c oxidase subunit I gene. The sequences obtained exhibited pairwise distances of ≤ 1.82% among them, and ~ 90% nucleotide identity with the homologous gene fragment in the morphologically similar Astylus variegatus Germar, 1824. The use of this molecular marker to explore the intraspecific variability of A. atromaculatus in central Argentina showed 21 different haplotypes, out of 32 individuals analyzed. A very high haplotype diversity (Hd = 0.962 ± 0.019) and a moderate nucleotide diversity (π = 0.00778 ± 0.00079) were recorded. The haplotype network displayed a diffuse structure due to the abundance of singletons and possible missing haplotypes, with the most common haplotype comprising only 15.6% of the specimens collected. Future research with increased sampling size and geographic coverage will allow for a better understanding of the population genetics of this pest, and consequently, for developing efficient management practices.